Pengaruh model pembelajaran direct instruction berbantuan media flash card terhadap keterampilan membaca permulaan kelas 1 sdn se-kecamatan panjatan - Mellinda Rizky Fahrizza; Siti Istiyati Istiyati (Universitas Sebelas Maret, 2025)
This study aims to determine the effect of applying the Direct Instruction learning model assisted by flash card media on the beginning reading skills of first-grade students at public elementary schools (SDN) in the Panjatan District during the 2024/2025 academic year. The research design used is a quasi-experimental design with a Nonequivalent Control Group Design. The research sample consisted of 69 first-grade students from SDN in the Panjatan District. The data collection technique employed a performance-based test. Preliminary data analysis included normality testing, homogeneity testing, and balance testing. The results of the independent sample t-test showed a significance level of Sig.<0.05, namely (0.000 < 0.05), indicating that H₀ is rejected and H₁ is accepted. The conclusion of this study is that the Direct Instruction learning model assisted by flash card media has a significant effect on improving the beginning reading skills of first-grade students at SDN in the Panjatan District during the 2024/2025 academic year.